ANALISIS HASIL PREDIKSI UNTUK PENGADAAN STOK BAHAN DENGAN METODE EOQ PADA TOKO O’AYAM GEPREK - Yuningsih, Yayuk; Bagus Setiawan, Ahmad; Putra Pamungkas, Danar (Universitas Nusantara PGRI Kediri, 2024)
This research discusses the design of a sales prediction and inventory procurement system using the Economic Order Quantity (EOQ) method at O'Ayam Geprek Restaurant. The aim of this study is to enhance the efficiency and effectiveness of inventory management, as well as to obtain optimal material restocking recommendations. The research is conducted through several stages, starting from needs analysis, system design, EOQ algorithm simulation, to application implementation. The EOQ method is chosen because it has been proven to provide accurate solutions in determining the optimal quantity of material orders. The research results indicate the successful implementation of the EOQ method at O'Ayam Geprek. The system can classify materials into two categories, namely Restock Yes and Restock No, based on predefined parameters. Evaluation of 21 materials during the October to November period shows that the system provides effective and efficient restocking recommendations. Alpha and beta functional testing also confirms the success of the implementation, with a user satisfaction level reaching 79.91%.